Penatalaksanaan Fisioterapi Pada Pasien Osteoarthritis Knee Dengan Modalitas Infrared, Tens (Transcuta Neus Electrical Nerve Stimulation) Dan Latihan Di RS. Universitas Sumatera Utara - Imam Ibrahim Nasution; Mustafa Al Haris (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Osteoarthritis is a progressive degenerative joint disease that causes pain, stiffness, and limited range of motion. Objective: To determine the implementation of physiotherapy in reducing pain, increasing joint range of motion, increasing muscle strength, and increasing functional activity in cases of right knee osteoarthritis using Infrared (IR) modalities, Tens (Transcutaneous electrical nerve stimulation), and exercise. Results: After 6 times the physiotherapy process, the results showed a decrease in pain, an increase in the range of motion of the joints, an increase in muscle strength, and an increase in functional activity. Conclusion: Management of physiotherapy with a diagnosis of knee osteoarthritis can reduce pain, increase joint range of motion, increase muscle strength, and increase functional activity.Keywords: Right knee osteoarthritis, Infrared (IR), and Tens (Transcutaneus electrical nerve stimulation)